PENGARUH STRATEGI PEMASARAN TERHADAP PENGEMBANGAN USAHA WARUNG MAKAN KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Novianti, Dita Dwi; Makhdalena, Makhdalena; R.M Riadi, R.M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The development of the food stall business in Pasir Turtle District, Indragiri Hulu Regency can be said to be a business that is not developing. This can be proven by the decrease in the number of food stall businesses from year to year. The decrease in the number of businesses was due to not implementing the right marketing strategy, which had an impact on the number of consumers they had and the income they received. This research aims to determine the influence of marketing strategy on business development. This research uses quantitative descriptive methods. The data collection methods used were interviews, questionnaires and documentation. The population in this study were all food stall business actors in Pasir Penyu District, Indragiri Hulu Regency, totaling 117 business actors. The sampling technique used purposive sampling so that a sample of 36 business actors was obtained. The data analysis technique used is simple regression analysis. Based on the results of data analysis, it is known that there is an influence of marketing strategy on business development. This can be seen from the results of data analysis which shows that the tcount value of 5,284 is greater than the ttable value of 2,032 and the resulting significant value is 0,000 <0,05. The contribution of marketing strategy to business development is 45,1%. For further research, it is hoped that it can expand the research object and can examine other factors that can influence business development so that the research results obtained can be better, more accurate, and obtain satisfactory results.Key Words: Marketing strategy, Business development